Endoscopic ultrasound-guided pancreatic drainage for treating a traumatic main pancreatic duct injury in a child - Masafumi Tanaka; Shogo Seo; Shigeto Ishii; Takanori Ochi; Go Miyano; Hiroyuki Koga; Toshio Fujisawa; Geoffrey J. Lane; Atsuyuki Yamataka; Hiroyuki Isayama (Elsevier, 2021)
A 10-year-old Japanese boy presented the day after a bicycle handlebar injury with mild abdominal pain. Computed tomography (CT) confirmed pancreatic transection and possible main pancreatic duct (MPD) injury because of a fluid collection around the pancreas. Conservative management (fasting, antibiotics, total parental nutrition, protease inhibitor) was initially successful, but an oral challenge with plain water on day 23 caused a relapse. CT identified a pancreatic pseudocyst. Endoscopic trans-papillary drainage was attempted but failed because the MPD was completely obstructed. Endoscopic ultrasound (EUS)-guided drainage of the pseudocyst with a lumen apposing metal stent (LAMS) was performed on day 29 via the stomach. On day 36, EUS-guided pancreatic drainage (EUS-PD) with a 5Fr plastic stent was performed via the stomach with rapid improvement in symptoms and elevated enzyme levels. Repeat oral challenge on day 39 was successful, the LAMS was removed on day 59 without recurrence. He was discharged well on day 69 and remains asymptomatic 20 months after treatment.Our case highlights the potential of minimally invasive endoscopic procedures as options for the non-surgical management of complete MPD disruption in a child. However, further research to develop dedicated pediatric endoscopic devices is required.